Genetic diversity of maize (Zea mays) accessions revealed by random amplifi ed polymorphic DNA markers - Zdenka Galova, Timea Kutka Hlozakova, Martin Vivodk, Zelmira Balazova, (Horticultural Biotechnology Research, 2015)
In the present study, random amplified polymorphic DNA (RAPD) markers were used to assess genetic diversityÂ of the maize genotypes. Five arbitrary random primers were used to determine RAPD polymorphism in the set ofÂ 20 maize genotypes. Amplification of genomic DNA of 20 genotypes, using RAPD analysis, yielded 33 fragments,Â with an average of 6.60 polymorphic fragments per primer. Number of amplified fragments ranged from 5 (OPA-02,Â OPB-08) to 10 (OPA-13), with the size of amplicons ranging from 250 to 2000 bp. The polymorphic informationÂ content value ranged from 0.751 (OPD-02) to 0.872 (OPA-13), with an average of 0.781 and diversity index valueÂ varied from 0.718 (OPB-08) to 0.874 (OPA-13) with an average of 0.790. The dendrogram based on hierarchicalÂ cluster analysis using unweighted pair group method with arithmetic average (UPGMA) algorithm was prepared.Â A dendrogram based on UPGMA analysis separated 20 maize genotypes into two clusters. RAPD markers areÂ useful in the assessment of maize diversity, the detection of the duplicate sample in genotypes collection, andÂ the selection of a core collection to enhance the efficiency of genotypes management for use in maize breedingÂ and conservation.Â